KOLABORASI GURU BIMBINGAN KONSELING DAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANGANI SISWA BERMASALAH DI MTs HIDAYATUL UMMAH MALAHAYU KABUPATEN BREBES - Entin Agustinawati (TASAMUH, 2020)
ABSTRACTThis research is a qualitative research using interviews, observation and documentation. The data analysis used in this research is descriptive qualitative. This study aims to describe collaboration, supporting and inhibiting factors and the impact of collaboration between Counseling Guidance teachers and Islamic Religious Education teachers in dealing with problematic students. The results showed that the collaboration between Counseling Guidance teachers and Islamic Religious Education teachers was carried out in terms of collaboration in carrying out joint recording of problematic students, taking handling steps, coordinating and cooperating in carrying out tasks, and creating joint activities for students. The supporting factors for the collaboration of Counseling Guidance Teachers and Islamic Education Teachers in dealing with problematic students at MTs Hidayatul Ummah Malahayu, Banjarharjo District, Brebes Regency are the formation of cooperation and coordination in assignments, clear madrasa programs, the cooperative role of parents and the community. The inhibiting factors are students who are bound to the community, parents who are less cooperative and respond making it difficult for the madrasa to communicate and open up student problems and solutions that will be applied by the madrasa. The impact of the collaboration between Guidance Counseling Teachers and Islamic Religious Education Teachers is better administration, more focused handling, encourage the active role of teachers and students in implementing madrasa programs, foster parent and community trust in madrasas, instill and restore students' confidence in socializing and socializing at home and at school or madrasah and open communication between students and parents. The negative impact is giving a bad impression to the madrasa from the parents of problematic students. Keywords: Collaboration, Counseling Guidance Teachers, Islamic Religious Education Teachers, Students with ProblemsABSTRAKPenelitian ini adalah penelitian kualitatif dengan menggunakan metode wawancara, observasi serta dokumentasi. Ada pun analisis data yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Penelitian ini bertujuan untuk mendeskripsikan tentang kolaborasi, faktor pendukung dan penghambat dan dampak kolaborasi adanya kolaborasi antara guru Bimbingan Konseling dan guru Pendidikan Agama Islam dalam menangani siswa bermasalah. Hasil penelitian menunjukkan bahwa kolaborasi antara guru Bimbingan Konseling dan Guru Pendidikan Agama Islam dilakukan dalam hal kolaborasi dalam melakukan pencatatan bersama mengenai siswa bermasalah, melakukan langkah-langkah penanganan, melakukan koodinasi dan kerjasama dalam melaksanakan tugas, dan menciptakan kegiatan bersama untuk siswa. Faktor pendukung kolaborasi Guru Bimbingan Konseling dan Guru Pendidikan Agama Islam dalam menangani siswa bermasalah di MTs Hidayatul Ummah Malahayu Kecamatan Banjarharjo Kabupaten Brebes adalah terbentuk kerjasama dan koordinasi dalam tugas, program madrasah yang jelas, peran orang tua dan masyarakat yang kooperatif. Faktor penghambat adalah siswa yang terikat kepada komunitas, orang tua yang kurang kooperatif dan merespon menyulitkan madrasah untuk berkomunikasi dan membuka permasalaan siswa dan penyelesaian yang akan diterapkan oleh madrasah. Dampak kolaborasi Guru Bimbingan Konseling dan Guru Pendidikan Agama Islam yaitu administrasi lebih baik, penanganan lebih terarah, mendorong peran aktif guru dan siswa dalam melaksanakan program madrasah, menumbuhkan kepercayaan orang tua dan masyarakat kepada madrasah, menanamkan dan mengembalikan rasa percaya diri siswa dalam bergaul dan bersosialisasi di rumah dan di sekolah atau madrasah dan membuka komunikasi siswa dan orang tua. Dampak negatif yaitu memberikan kesan tidak baik bagi madrasah dari orang tua siswa bermasalah. Kata Kunci : Kolaborasi, Guru Bimbingan Konseling, Guru Pendidikan Agama Islam, Siswa Bermasalah